Between Black mothers and daughters: a critical intergenerational duoethnography on the silence of health disparities and hope of loud healing - Winfield, Asha S.; Hickerson, Hope; Doub, Deshara C.; Winfield, Ann R.; McPhatter, Brigitte (Frontiers in Communication, 2024)
Introduction Black American women's health outcomes have been altered by a number of factors. Those factors include social determinants of health, lack of culturally competent healthcare providers, and generations of medical racism leading to prolonged pain, delayed care, and sometimes, untimely deaths. Methods This original research article centers Southern Black women's lived experiences through family storytelling. We explored generations of health narratives in regard to age, region, and at times, their own acts of silence. Building from theorizing on loud healing, two Black daughters turned the mic on for their mothers by engaging in a critical intergenerational double duoethnography to discuss decades of healing over a 3 months long conversation (in person, over the phone, and on video chat). Results The analysis of the interviews/dialogue between Black mothers and daughters identified several themes connected to loud healing: (1) some healths lessons are quietly taught from intergenerational trauma; (2) the silencing of Black matriarchs occurs in generations not just spirals; (3) loud healing is a faith-filled call to action; (4) mothers and daughters help turn the mic on for each other; (5) Loud healing is affirming and produces visibility; (6) the body teaches culturally competent health lessons; (7) Trusting loud healing to leave the mic on and door open. Discussion Our collective and individual lived experiences reveal the very real impacts of culture, identity, and power on Black women's health and storytelling. By interrogating the past with our stories, this group of Black mothers and daughters represents three generations of medical erasures, amplification of voice, and the need for loud healing for loud, tangible change.